1976
DOI: 10.1021/jf60208a010
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosopyrrolidine formation in fried bacon

Abstract: HWANG, ROSEN remarkably from that obtained by steam distillation. Even higher boiling products with a retention index up to 1700 can be isolated by this method which proves to be very mild and produces practically no artefacts. It has been applied successfully to leek, apples (Dirinck et al., 1975), and tomatoes (Dirinck et al., 1976) and can be used in evaluating natural flavor quality of fruits and vegetables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
2

Year Published

1978
1978
2006
2006

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 17 publications
1
3
2
Order By: Relevance
“…From the data presented in this paper, statistical analysis (comparison tests and analysis of variance techniques) of the differences in amino acid content before and after frying and NA concentration found after frying showed no significant correlation. Contrary to what has recently been reported (Bharucha et al, 1979;Coleman, 1978;and Hwang and Rosen, 1976), our data indicate that the NDMA and NPYR contents of fried bacon are independent of the concentration of free amino acids. Nitrosamine concentration was not significantly affected when the amino acid source, including proline, was decreased nor when the availability of free amino acids increased significantly.…”
Section: Resultscontrasting
confidence: 99%
“…From the data presented in this paper, statistical analysis (comparison tests and analysis of variance techniques) of the differences in amino acid content before and after frying and NA concentration found after frying showed no significant correlation. Contrary to what has recently been reported (Bharucha et al, 1979;Coleman, 1978;and Hwang and Rosen, 1976), our data indicate that the NDMA and NPYR contents of fried bacon are independent of the concentration of free amino acids. Nitrosamine concentration was not significantly affected when the amino acid source, including proline, was decreased nor when the availability of free amino acids increased significantly.…”
Section: Resultscontrasting
confidence: 99%
“…Although the isotope labeling studies of Hwang and Rosen (1976) indicated that preformed NPRO in uncooked meat may be the major precursor of nitrosopyrrolidine in cooked meat, the levels of NPRO found in the present study would be too low to account for the high levels of nitrosopyrrolidine in cooked samples. However, as was found in the commercial bologna sample, the NPRO content can be increased three orders of magnitude in 4 h by the addition of a large excess of nitrite.…”
Section: And Discussioncontrasting
confidence: 77%
“…has also established a linear relationship between the level of free proline present at cooking with the level of NPYR found in cook-out fat. By working with C14 labeled proline, Hwang and Rosen (1976) have similarly come to the conclusion that proline is the major precursor of NPYR. The conversion of proline to NPYR could conceivably occur by either of the two pathways shown in Scheme I.…”
Section: Resultsmentioning
confidence: 99%